HAMBATAN PERLEKATAN Salmonella typhi PADA ENTEROSIT TIKUS PUTIH (WISTAR) OLEH ANTIBODI POLIKLONAL ANTI PROTEIN HEMAGLUTININ SUB UNIT PILLI - Sri Darmawanti (JURNAL LITBANG, 2007)
Typhoid Dengue is a disease coused by Salmonella typhy bacteria, and constitutes a seriotts disea"^e in Indonesia ancl in other cleveloping countries. This is due to the high prevalence of the disease (0.36% - 0.81%) per annum and due to vurious handicaps in term of clinical description, diagnosis and cwe of this clisease. The prevention effort that has heen token by preventing the incidence of initial pathogenesis. Therefore. it is necessary to find out the pathogen factor which plays a role in the entry of such bacteria into inlestines as the initial palhogenesis. The general oh.iective of this re.search i,s to arml1,:e the handiccrp in attachtrtg the Salntgnella gtphi on the v,hite mice enterosit (Wistar) by polyclonal crntibocty ofanti protein hemaglutinin of'sub unit pilli 36 kDu crnd 18.6 kDa. The specific objectit'es of tltis research are to (l) .find out the attachnrenr paffern of'Salmonella t..vphi on the white mice enterosit (Wistar) (2) find out the capability of attachment ltandicap of bacteria cell on tlte enlerosit hy plovclonnal antibody of anti protein hemugluinin. The research was conducted in several stages, nantely the attachment testing by using the Nagayama at al. method, 1995 in which the testing nsed enterosit from white mice (LVistor) intestinal isolation that was performed according to Weiser (1973), the testing of handicap of bacterial attachment on the enterosit by polyclonal antibody of anti protein hemaglutinin of sub unit pilli 36 kDa and 18.6 kDa. The research showed that the polyclonal antibody; of anti protein hemaglulinin of sub unit pilli 36 kDa uncl 18.6 kDa fi'om kilmonella t.vphi ccm,slow down the bacterial attachmen on white mice enterttsit (Wistar) Key word: Salmonella typhi, Polyclonal Antibody, Hemaglutinin